Associations between serum cystatin C and fall reports in an Elderly population - Jing Han; Ruiyun Wang; Lijuan Bai; Yun Liu; Man Liao; Liting Zhang; Lihua Liu; Benling Qi (Scientific Reports)
Abstract Fall is common in the elderly, and chronic kidney disease is considered a major risk factor. Serum creatinine (Cre) and cystatin C (Cys C) are commonly used biomarkers for renal function, while the ratio of Cre to Cys C, known as the sarcopenia index (SI), provides insights into muscle health. This study investigates the relationships between Cre, Cys C, estimated glomerular filtration rates (eGFR), SI, and self-reported falls using National Health and Nutrition Examination Survey (NHANES) data. We included 4,272 older adults with eGFR > 30mL/min/1.73m2 from NHANES (1999 to 2004) and divided them into the fall and non-fall groups based on the questionnaires. Correlations were assessed using restricted cubic spline, weighted generalized linear regression models. Multi-factor logistic regression analysis identified serum Cys C as significantly associated with falls (all participants: OR 1.16, 95% CI: 1.09 to 1.23, p < 0.001; participants with eGFR > 75 mL/min/1.73m2: OR 1.17, 95% CI: 1.05 to 1.30, p < 0.001,). In contrast, Cre and eGFR were not significant after adjustments; SI showed marginal significance (p = 0.045). Cys C is significantly associated with fall risk in older adults, demonstrating a positive linear relationship with self-reported falls.